2013
DOI: 10.1107/s1600536813028602
|View full text |Cite
|
Sign up to set email alerts
|

Sodium selenite pentahydrate, Na2SeO3·5H2O

Abstract: Key indicators: single-crystal X-ray study; T = 100 K; mean (Se-O) = 0.001 Å; R factor = 0.015; wR factor = 0.039; data-to-parameter ratio = 16.9.In the crystal structure of Na 2 SeO 3 Á5H 2 O [disodium selenate(IV) pentahydrate], two Se, two selenite O atoms and one water O atom are located on a mirror plane, and one water O atom is located on a twofold rotation axis. The coordination of one Na + cation is distorted trigonal bipyramidal, formed by three equatorial H 2 O ligands and two axial selenite O atoms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
(10 reference statements)
1
6
0
Order By: Relevance
“…The [NaO 6 ] octahedra in these two salts share common faces and edges but no vertices. As pointed out by Philippot et al (1979) for Na 2 TeO 3 (H 2 O) 5 and confirmed also for Na 2 SeO 3 (H 2 O) 5 (Mereiter, 2013), the electron lone pair of Se and Te in these structures shows no attracting interactions with neighbouring H atoms. This might be one reason why hydrates of Na 2 SeO 3 and Na 2 TeO 3 do not crystallize in the Na 2 SO 3 (H 2 O) 7 structure and vice versa.…”
Section: àsupporting
confidence: 59%
See 1 more Smart Citation
“…The [NaO 6 ] octahedra in these two salts share common faces and edges but no vertices. As pointed out by Philippot et al (1979) for Na 2 TeO 3 (H 2 O) 5 and confirmed also for Na 2 SeO 3 (H 2 O) 5 (Mereiter, 2013), the electron lone pair of Se and Te in these structures shows no attracting interactions with neighbouring H atoms. This might be one reason why hydrates of Na 2 SeO 3 and Na 2 TeO 3 do not crystallize in the Na 2 SO 3 (H 2 O) 7 structure and vice versa.…”
Section: àsupporting
confidence: 59%
“…For Na 2 SeO 3 , the anhydrous form (P2 1 /c, Z = 4) is made up from [NaO 6 ] octahedra and trigonal-pyramidal SeO 3 2À anions (Wickleder, 2002), and is isotypic with Na 2 TeO 3 (Masse et al, 1980). Hydrated forms are known only for the pentahydrates Na 2 SeO 3 (H 2 O) 5 (Mereiter, 2013) and Na 2 TeO 3 (H 2 O) 5 (Philippot et al, 1979) that are, surprisingly, not isotypic (Pbcm, with Z = 8, and C2/c, with Z = 8, respectively). These structures are based on two-or three-dimensional assemblies of [NaO 5 ] polyhedra (Se) and [NaO 6 ] octahedra (Se and Te), to which SeO 3 /TeO 3 groups are bonded via two (Se) or one (Te) O atom.…”
Section: àmentioning
confidence: 99%
“…Na 2 SeO 3 was always present in a rather large impurity phase (almost 30% in this case). Besides Na 2 SeO 3 , the additional reflections present could not be attributed to any known phases nor to the previously reported phase of Na 2 SeO 3 ·5H 2 O (Mereiter, 2013). This suggested the presence of either a new hydrate of Na 2 SeO 3 , or a new polymorph.…”
Section: Methodsmentioning
confidence: 49%
“…The crystal structures of various Na 2 X O 3 ·5H 2 O ( X = HP (hydrogen phosphorus), Te, Se) have been reported in the past (Colton and Henn, 1971; Philippot et al, 1979; Mereiter, 2013) from single crystal diffraction. Among the series one composition is missing which is the sulfite counterpart Na 2 SO 3 ·5H 2 O.…”
Section: Introductionmentioning
confidence: 98%
“…Although it is more usual to find Na + in octahedral coordination, there are abundant examples of Na + in five-fold coordination, including instances where the NaO 5 polyhedron adopts a square-pyramidal arrangement (Beurskens & Jeffrey, 1961;Císařová ;Sharma et al, 2005;Smith & Wermuth, 2014;Aksenov et al, 2014) or the alternative trigonal-bipyramidal arrangement (Mereiter, 2013;Smith, 2013). A similar combination of NaO 6 and NaO 5 polyhedra to that found in the title compounds occurs in the closely-related hydrates Na 2 CrO 4 Á1.5H 2 O and Na 2 SeO 4 Á1.5H 2 O (Kahlenberg, 2012;Weil & Bonneau, 2014).…”
Section: Structural Commentarymentioning
confidence: 99%